DI-009 Health literacy to prevent adverse drug events: cetuximab dermatological toxicity. (24th February 2014) - Sgarlata, D; Guzzardi, S; Avola, N; Valerio, A; Spadaro, D; Marletta, E; Regolo, S; Cacciaguerra, G
Abstract : Background: Anti-EGFR chemotherapy drugs cause skin toxicity due to high numbers of receptors in keratinocytes of the epidermis, sebaceous glands, epithelial hair follicles. Cetuximab treatment for metastatic colorectal cancer causes rash (1st to 4th degree), xerosis and nail changes. When the symptoms are severe (3rd degree rash extended to 50% of the body surface) treatment must be interrupted and, if symptoms don't subside, permanently discontinued. High incidence of rash makes it necessary to reduce the severe symptoms to prevent treatment disruptions. Clinical evidence suggests that prophylactic use of vitamin K prevents and reduces cetuximab skin toxicity. Purpose: To support the patient in managing cetuximab dermatological toxicities to allow treatment to continue. Materials and methods: In the Oncology departments of Azienda Sanitaria Provinciale, Siracusa, Italy, a cream containing urea and vitamin K1 (0.1%) is supplied to the patient after each chemotherapy treatment. The cream is accompanied by specific instructions, prepared by the Pharmacovigilance team, (apply 2 times a day on the face and chest) and preventive indications: use sunscreen, moisturise the skin with emollient creams without alcohol or tocopherol acetate, avoid tight shoes, prevent beard growth, don't use electric shavers. Results: From September 2012 to February 2013, 12 patients treated with cetuximab received the cream and behavioural instructions. There were 4 women, 8 men, mean age 63, no patients used antibiotic creams. All patients had a peak of skin toxicity around the 3rd week of treatment, with a rash of 70% (moderate); use of the cream persuaded the rash to gradually reduce, limiting toxicity to 1st degree. Conclusions: The information provided to patients meant that nobody suspended treatment. 80% of patients reported that the cream had reduced the pain and itching. Women demonstrated greater compliance with the instructions provided. The results show that the proper information can prevent predictable adverse drug events, ensuring continuity of care. No conflict of interest.